2005
DOI: 10.1081/dct-200039696
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Lead Exposure Induces Depressive-like Behavior in Female Rats

Abstract: The involvement of neurotoxicants in the etiology of emotional pathologies is becoming an issue in neurotoxicology. Lead (Pb) exposure during childhood has been associated with increased impulsivity, aggressivity, and delinquency. Considering the paucity of experimental studies investigating the involvement of developmental Pb exposure in emotional disorders, our objective was to investigate whether Pb exposure during pregnancy and/or lactation could be related to depressive symptoms in adult male and female r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Female rats exposed to Pb through gestation and lactation were more impaired in reference memory than male rats with similar Pb exposures (Jett et al, 1997). De Souza Lisboa et al (2005) reported that exposure to Pb during both pregnancy and lactation led to depressive-like behavior (detected in the forced swimming test) in female but not male rats. The influence of sex as an effect modifier of childhood Pb poisoning has also received little systematic attention.…”
Section: Discussionmentioning
confidence: 99%
“…Female rats exposed to Pb through gestation and lactation were more impaired in reference memory than male rats with similar Pb exposures (Jett et al, 1997). De Souza Lisboa et al (2005) reported that exposure to Pb during both pregnancy and lactation led to depressive-like behavior (detected in the forced swimming test) in female but not male rats. The influence of sex as an effect modifier of childhood Pb poisoning has also received little systematic attention.…”
Section: Discussionmentioning
confidence: 99%
“…Other possible mechanisms include direct effects on the hypothalamus ( Bratton et al 1994 ) or pituitary gland ( Huseman et al 1987 ), changes in brain catecholamine levels within the hypothalamus ( Virgolini et al 2005 ), or alterations to cytokine levels ( Hemdan et al 2005 ) and corresponding HPA feedback ( Marx et al 1998 ). Pb exposure could also indirectly affect cortisol levels via changes in body weight ( Scavo et al 1988 ) or nutrition ( Giovannini et al 1990 ) produced by Pb-induced mood changes ( Lisboa et al 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…In spite of its limitations, the oral administration of Pb to the pregnant mother and/or infant is the animal model most frequently used to evaluate the consequences of chronic exposure to low levels of Pb during development. The model allows for behavioral evaluation of the subjects after 70–90 days of exposure and age (de Souza Lisboa et al, 2005 ; Weston et al, 2014 ). Additionally, this scheme of exposure enables the evaluation of epigenetic effects (DNA methylation, histone modifications, and ncRNAs regulation) induced by exposure to Pb.…”
Section: How To Address the Problem Of Neurological Alterations Due Tmentioning
confidence: 99%